2018
DOI: 10.1371/journal.pone.0197005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characterization of Escherichia coli isolated from the Upper Oconee Watershed in Northeast Georgia

Abstract: Surface waters are important sources of water for drinking, industrial, agricultural, and recreational uses; hence, contamination of water by fecal, pathogenic, or antimicrobial resistant (AR) bacteria is a major environmental and public health concern. However, very little data is available on prevalence of these bacteria in surface water throughout a watershed. This study aimed to characterize Escherichia coli present in the Upper Oconee Watershed, a mixed-use watershed in Athens, GA, USA for potential patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…and the exact locations of the sites, along with the GPS coordinates, are in Table . Interestingly, a complimentary study conducted on the same sampling sites showed that Enteropathogenic E. coli and AR E. coli isolates were recovered from 22 of the 35 MDR Enterococcus ‐positive sites (Cho et al ). This finding shows that there are sites within the Upper Oconee watershed that contribute towards the spread of pathogenic and AR bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and the exact locations of the sites, along with the GPS coordinates, are in Table . Interestingly, a complimentary study conducted on the same sampling sites showed that Enteropathogenic E. coli and AR E. coli isolates were recovered from 22 of the 35 MDR Enterococcus ‐positive sites (Cho et al ). This finding shows that there are sites within the Upper Oconee watershed that contribute towards the spread of pathogenic and AR bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Filtration and enrichment of water samples were performed as previously described (Cho et al ). Briefly, 0·5 g of cellulose filter powder (Aqua Dew ™ , Lahore, Pakistan) was added to water samples (1 L), which was then filtered onto 47‐mm glass fibre filters (Pall Corporation, Ann Arbor, MI).…”
Section: Methodsmentioning
confidence: 99%
“…The investigative process for the Urban Water Quality course includes the common methods used by monitoring and regulatory agencies. Urban watersheds are under increasing pressure due to population growth and land development, with a strong impact on the microbial community (28,29). Students select local water resources to sample, which removes a bias for neighborhoods with greater financial or political interest that can be present for typical monitoring programs.…”
Section: Urban Water Qualitymentioning
confidence: 99%
“…Jain (2019) reported that the Ganga river had been polluted by a large number of resistant antibiotics bacteria which was suspected from some waste discharged from households, drug manufacturing units, hospitals, and poultry industries. Another study was done by Cho et al (2018) suggested that the other possible human's coliform sources include sewage leaks, failing septic tanks, municipal, residential, medical, and industrial waste facilities and also animal sources include runoffs from animal farms, land application of animal manure, pet wastes from parks, and wildlife; all of them are potentially increase the spreads of the hazardous contaminants.…”
Section: Introductionmentioning
confidence: 99%